The 2-point method: a quick, accurate, and repeatable approach to estimate ultrasound-derived quadriceps femoris cross-sectional area - Hernández-Belmonte, A.; Martínez-Cava, A.; Pallarés, J. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To analyze the feasibility of the 2-point method for estimating ultrasound-derived quadriceps femoris cross-sectional area (QUADACSA). First, (1) the agreement between QUADACSA measured by panoramic ultrasound and magnetic resonance imaging (MRI) was studied, and thereafter, we examined 2 approaches of the 2-point method in terms of (2) estimation errors and (3) test-retest repeatability.